Enriching 1,8-Cineole Content in Eucalyptus camaldulensis D. Raw Essential Oil: An Investigation on Optimizing Vacuum Fractional Distillation Process - Le, Tien Xuan; Nguyen, Minh Nhat; Le, Trung Minh; Pham, Minh Chau Vu (Universitas Gadjah Mada, 2025)
This study addressed the gap in optimizing the 1,8-cineole content in Eucalyptus camaldulensis essential oil, an area with a limited focus in existing literature. While previous research has explored distillation methods for essential oils, this study is the first to systematically investigate the effects of key operational parameters on cineole enhancement using batch vacuum fractional distillation. The optimization process was carried out using a single–factor method focusing on operating pressures (60, 80, 100, 120, 140, and 160 mmHg), column types (Vigreux and Hempel), packing materials (wire mesh, large strings, small strings), and column heights (300, 400, 500, and 600 mm). After each distillation experiment, the essential oil samples were analyzed using GC-MS to quantify the concentration of 1,8-cineole and other components. The best result, achieved at 60 mmHg with a 500 mm Hempel column packed with small metal helixes (2 × 10 mm), increased 1,8-cineole content from 47.9% to 74.6%, with 97% recovery and over 60% yield. These findings highlight the impact of distillation parameters on cineole concentration, marking a 1.5-fold improvement. This optimized distillation process offers an efficient alternative for producing high-bioactivity cineole oil, with potential pharmaceutical and personal care applications, reducing reliance on complex synthesis.